The Effects of One-Sided vs. Two-Sided Review Valence on Electronic Word of Mouth (e-WOM): The Moderating Role of Sponsorship Presence - Park, Jihye; Yi, Youjae; Kang, Dawon (ASIA MARKETING JOURNAL, 2019)
Prior studies on the effects of online consumer reviews have mainly focused on review valence, but little research has investigated how two–sided (both positive and negative) and one-sided (only positive) reviews influence consumers’ response to online review. In addition, little attention has been paid to how sponsorship presence (firm-sponsored reviews vs. consumer-voluntary reviews) influences individuals’ attitude toward online review. Unlike consumer-voluntary reviews without any monetary incentive, firm-sponsored reviews include messages about brands providing monetary compensation. This study examines whether review valence (two-sidedness vs. onesidedness) influences attitude toward online review via its influence on review credibility. Further, this study examines whether sponsorship presence affects when review valence influences attitude toward review. Thus, this research investigates the effect of review valence on attitude toward review and the moderating role of sponsorship presence in the relationship between review valence and attitude toward review. The first experiment reveals that attitude toward review is more favorable when the review is two-sided (vs. one-sided). The second study demonstrates that differences between the two-sided and the one-sided review occur only for firm-sponsored reviews, not for consumer-voluntary reviews. The theoretical and practical implications are also discussed.